Synthesis of novel 3 '-deoxy-3 '-C-hydroxymethyl nucleosides with conformationally rigid sugar moiety as potential antiviral agents - Chun, MW; Kim, MJ; Jo, UH; Kim, JH; Kim, HD; Jeong, LS (MARCEL DEKKER INC, 2001)
Based on the fact that the ring expanded 3'-C-hydroxymethyl analogue of oxetanocin A exhibited potent antiviral activity, two types of conformationally rigid 3'-C-hydroxymethyl derivatives in which 2'-hydroxyl group is linked to the 4'-position or to the 6'-position were synthesized starting from 1,2;5,6-di-O-isopropylidene-D-glucose, respectively.
Keywords: OXETANOCIN